Opportunities and Challenges of Acquiring Arabic as a Second Language (Psycholinguistic Studies in Arabic Language Learning) - Malikh, Majda Qudsiyatul; Saefullah, Ihsan Muhammad (Mayada: al-Multaqa al-Ilmy al-Alamy lil-Dirasat al-Arabiyah, 2024)
تهدف هذه الدراسة إلى تحليل فرص وتحديات اكتساب اللغة العربية كلغة ثانية لدى طلاب برنامج دراسة تعليم اللغة العربية في جامعة عمان مولانا مالك إبراهيم ملانج. بالإضافة إلى ذلك، تعكس هذه الدراسة أيضا المبادرات التي اتخذها الطلاب للتغلب على محدودية معرفتهم ومهاراتهم في اللغة العربية. باستخدام المنهج النوعي الوصفي وباستخدام نوع من البحث الميداني، تم جمع البيانات من خلال الملاحظة والمقابلات. تتضمن مصادر البيانات الأولية مشاركة الطلاب وقادة برنامج دراسة تعليم اللغة العربية كأطراف لها دور في السياسة، بينما يتم الحصول على البيانات الثانوية من الوثائق والمجلات ذات الصلة. أظهرت النتائج أن هناك ثلاث فرص يمكن أن يستغلها الطلاب في عملية اكتساب اللغة العربية كلغة ثانية، وهي: (1) إثراء مواد المناهج الدراسية، (2) الاستفادة من بيئة التعلم، (3) الدعم الأكاديمي. من ناحية أخرى، تشمل التحديات التي يواجهها الطلاب: (1) التدخل اللغوي، (2) الاختلافات الكبيرة بين اللغة الأولى واللغة الثانية، و (3) تنوع الخلفيات التعليمية للطلاب. تصف هذه الدراسة أيضا ثلاث خطوات اتخذها الطلاب للتغلب على التأخر في المعرفة والمهارات العربية، وهي: (1) المشاركة بنشاط في أنشطة التعلم الجماعي باللغة العربية، (2) المشاركة في أنشطة اللغة شبه المنظمة (BSO) في الحرم الجامعي، و (3) طلب دعم إضافي من خلال دروس اللغة العربية الخاصة خارج بيئة الحرم الجامعي. A This study aims to analyze the opportunities and challenges of acquiring Arabic as a Second Language in students of the Arabic Language Education Study Program at UIN Maulana Malik Ibrahim Malang. In addition, this study also reflects the initiatives taken by students to overcome the limitations of their knowledge and skills of Arabic. With a qualitative approach descriptive method and using a type of field research, data were collected through observation and interviews. Primary data sources involve the participation of students and leaders of the Arabic Language Education Study Program as parties who have a role in policy, while secondary data are obtained from related documentation and journals. The results showed that there are three opportunities that can be utilized by students in the process of acquiring Arabic as a second language, namely: (1) Enrichment of curriculum materials, (2) Utilization of learning environment, and (3) Academic support. On the other hand, the challenges faced by students involve: (1) Language interference, (2) Significant differences between First Language and Second Language, and (3) Diversity of students' educational backgrounds. This study also describes three steps taken by students to overcome the lag in Arabic knowledge and skills, namely: (1) Actively participate in Arabic group learning activities, (2) Participate in language Semi-Organization (BSO) activities on campus, and (3) Seek additional support through private Arabic lessons outside the campus environment.